Cardiac oxidative damage in mice following exposure to nanoparticulate titanium dioxide. Issue 11 (2nd April 2013) - Sheng, Lei; Wang, Xiaochun; Sang, Xuezi; Ze, Yuguan; Zhao, Xiaoyang; Liu, Dong; Gui, Suxin; Sun, Qingqing; Cheng, Jie; Cheng, Zhe; Hu, Renping; Wang, Ling; et al.
<x xml:space="preserve">Abstract</x> Nanoparticulate titanium dioxide (nano‐TiO2) is a widely used powerful nanoparticulate material with high stability, anticorrosion, and photocatalytic property. However, it is possible that during nano‐TiO2 exposure, there may be negative effects on cardiovascular system in intoxicated mice. The present study was therefore undertaken to determine nano‐TiO2‐induced oxidative stress and to determine whether nano‐TiO2 intoxication alters the antioxidant system in the mouse heart exposed to 2.5, 5, and 10 mg/kg body weight nano‐TiO2 for 90 consecutive days. The findings showed that long‐term exposure to nano‐TiO2 resulted in obvious titanium accumulation in heart, in turn led to sparse cardiac muscle fibers, inflammatory response, cell necrosis, and cardiac biochemical dysfunction. Nano‐TiO2 exposure promoted remarkably reactive oxygen species production such as superoxide radicals, hydrogen peroxide, and increased malondialdehyde, carbonyl and 8‐OHdG levels as degradation products of lipid, protein, and DNA peroxidation in heart. Furthermore, nano‐TiO2 exposure attenuated the activities of antioxidative enzymes, such as superoxide dismutase, ascorbate peroxidase, glutathione reductase, glutathione‐S‐transferase, and levels of antioxidants including ascorbic acid, glutathione, and thiol in heart. Therefore, TiO2 NPs exposure may impair cardiovascular system in mice, and attention should be aroused on the application of nano‐TiO2 and their potential long‐term exposure effects especially on human beings. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3238–3246, 2013.